Trade and trade policies in Eastern and Southern Africa - Subramanian, Arvind...[et al] (IMF WashingtonUS, 2000)
Analyzes trade and trade policy developments in the countries of eastern and southern Africa during the 1990s, covering regional and multilateral integration issues, and the interaction between trade policies and macroeconomic conditions. Discusses the main challenges these countries face as they enter a new decade.